Ameliorative effects of canolol against acrylamide toxicity in PC12 cells through modulating MAPKs pathway and autophagy. (December 2020) - Xia, Xiaoyang; Zhang, Zhen; Zheng, Chang; Deng, Qianchun; Zheng, Mingming; Han, Ling; Xiang, Xia
Graphical abstract: Canolol extracted from rapeseed oi attenuated the acrylamide (ACR)-induced toxicity in PC12 cells by regulating activation of MAPKs pathway and autophagy. Highlights: Canolol attenuated ACR-induced toxicity in PC12 cells. Canolol suppressed ACR-induced activation of MAPKs pathway. Canolol blocked ACR-induced activation of autophagy. Abstract: Acrylamide (ACR), widely present in heat treatment of starchy foods, has attracted much attention in chronic neurotoxin. Canolol is a crucial phenolic compound and generated in rapeseed oil during microwave pressing. The present study aimed to reveal the ameliorative effects of canolol against ACR-induced toxicity in PC12 cells and the underlying mechanism. Cells pretreated with canolol inhibited ACR-exerted cytotoxicity and cell apoptosis. Canolol attenuated the increase of intracellular ROS and MDA level induced by ACR, and restored ACR-triggered depletion of glutathione content and mitochondrial membrane potential. Furthermore, canolol upregulated expressions of phosphorylated ERK1/2 protein, and downregulated phosphorylated p38 and JNK proteins after 24 h pretreatment in ACR-treated PC12 cells. Notably, ACR-stimulated autophagy activation was hindered by canolol in counteracting ACR-exerted LC-3 conversion and promoting the expression of p62 protein. Our study demonstrated that canolol prevented ACR damage involving MAPKs pathway and autophagy in PC12 cells, providing a potential application of canolol for ACR toxicity.